Crisis Management in Dakwah: A Critical Review of Islamic Legal Strategies During the Christian Conquest of North West Iberia Africa - Carimo Mohomed (Maddah: Journal of Advanced Da'wah Management Research, 2026)
The fall of Islamic rule in Iberia and North Africa presented a monumental crisis for the Muslim community, requiring strategic management to preserve faith and social cohesion under Christian occupation. This study aims to critically review Islamic legal strategies specifically fatwas as instruments of crisis management in dakwah during the Christian conquest of North West Africa and Iberia. This research employs a qualitative historical approach and literature review, critically analyzing the primary arguments and historical contexts presented in Jocelyn Hendrickson's "Leaving Iberia," alongside 15th and 16th-century North African fatwas. The findings reveal that North African jurists utilized fatwas not merely as legal rulings but as strategic dakwah management tools to counter Christian expansion, manage clandestine religious transmission (covert dakwah), and enforce emigration (hijrah) as a survival strategy. These legal responses successfully preserved Islamic identity during severe socio-political upheavals and maintained lasting authority into the modern colonial era, proving that legal discourse is a vital component of crisis management in Islamic preaching.